Pengaruh Content Marketing dan Online Customer Review Terhadap Keputusan Pembelian Online pada Komunitas Pelajar dan Mahasiswa Kabupaten Berau (KPMKB) di Samarinda - Artika, Riska Nur; Haidar, Kadori; Sutrisno, Sutrisno (Journal of Economic Education and Entrepreneurship Studies, 2024)
Technology can change the human lifestyle, originally buying goods offline, now with e-commerce it can be online. This study aims to determine the effect of Content Marketing and Online Customer Review on Online Purchasing Decisions at KPMKB in Samarinda. This type of quantitative descriptive research uses data collection techniques through distributing questionnaires, with 83 respondents. The analysis technique used is multiple linear regression analysis. The results showed that the calculation of the t test on Content Marketing and Online Customer Review had a partially significant effect on Online Purchasing Decisions at KPMKB in Samarinda. Fhitung test results Content Marketing and Online Customer Review simultaneously and significantly affect online purchasing decisions at KPMKB in Samarinda. The magnitude of the influence of the two independent variables on the dependent variable is around 79.1%.